(untitled) (Journal of history, 2017)
The article is devoted to the analysis of Eurasianism of N. Nazarbayev. The author considers the concept of "Eurasianism" in history and in the development of integration of countries in the post-Soviet space. In this paper, the author explains the reasons for the lack of interest of the leadership of Russia and other CIS countries to the initiative of the Kazakh leader in the 1990s, and a return to the Eurasian concept in the early 2000s, and the development of this idea since the 2010s. Until now. The author also identifies the factors under the influence of which Kazakhstan plays a special role in the process of integration of the states of the Eurasian space. The relationship of states in the post-Soviet space and the prospect of strengthening integration between them.